Inside-out flowers of Lacandonia brasiliana (Triuridaceae) provide new insights into fundamental aspects of floral patterning - Rudall, Paula J.; Alves, Marccus; Sajo, Maria das Gracas [UNESP] (Peerj Inc, 2016)
Background and Aims. A recently described Brazilian species, Lacandonia brasiliana, shares with its longer established putative sister species from Mexico, L. schismatica, inverted floral patterning (carpels surrounding stamens) that is almost unique among angiosperms. We present a detailed ontogenetic study of L. brasiliana for comparison with other members of the tribe Triurideae (Triuridaceae) to explore the possible evolutionary origins of inside-out'' flowers. Methods. Wild-source populations of L. brasiliana were compared morphologically and ontogenetically with related species of Triurideae, using light and scanning electron microscopy. Key Results. Relatively few morphological differences separate flowers of L. brasiliana and L. schismatica. Both species have tepals with late-developing subapical appendages. In both species, the three central (almost sessile) anthers develop precociously with respect to the carpels; the anthers remain closed, and fertilization is achieved via pollen-tube growth from germinating pollen grains of the same cleistogamous flower. Carpels are initiated on fascicles. Conclusions. The close similarity between the two Lacandonia species makes it unlikely that they arose independently from two separate homeotic transformation events; they could either represent sister species or two populations of a single disjunct species. Our study underlines the problematic generic and species boundaries within Triurideae. We present an evolutionary scenario of character evolution in Triuridaceae. The inside-out Lacandonia flower could have resulted from a stabilized homeotic transformation; this hypothesis is not in conflict with constrasting theories of the origin of the Triuridaceae flower, which coincided with a shift to unisexuality. The unisexual yet highly plastic flowers that are typical of Triuridaceae could have pre-adapted the origin of the extraordinary Lacandonia morphology.
Keywords: Lacandonia; Evolutionary transformation; Inside-out flowers; Mycoheterotrophs; Unisexuality; Triuridaceae; Pandanales